The decomposition algorithm of the computing resources distribution in a wireless computer network - Жуков, И. А.; Печурин, Н. К.; Кондратова, Л. П.; Печурин, С. Н. (Problems of Informatization and Control, 2015)
In this paper there is researched the possibility of solving the problem to distributed the computingresources in a wireless network using a two-lier Danzig-Wolfe decomposition. By bringing theconstraint matrix for the mathematical model of the considered problem in the block-diagonalstructure form with separating the restrictions’ independent blocks, this way provides a solution to thelower dimension problem, which provides compatibility with the result of a classical flow algorithmsexecuting